DREAM*HOPING INTO FUTURES: black women in the harlem renaissance and afrofuturism. Issue 3 (4th July 2022) - Arndt, Susan; Soltani, Omid
Abstract: The Harlem Renaissance espoused the modernist belief in radical new beginnings and the celebration of (aesthetic) interventions into old certainties, while resisting the "monologism" (Bakhtin) of white Western modernity and modernism. As a result, the Harlem Renaissance strived towards new futureS, nourished by dreams and hopes. The same endeavour was echoed but handled differently by the (post)modernist aesthetic strategy of Afrofuturism. Both the Harlem Renaissance and Afrofuturism's conceptions of dreams and hopes, in given intersections (hence dream*hopes, the asterisk marking the fluid entanglement of the two concepts) and as agents of future-making, are at the fore of this article. Framed by critical race theory and underpinned by "future" as a critical category of analysis, it starts off with an examination of dream*hoping agencies of future-making in view of both the Harlem Renaissance and Afrofuturism. In doing so, Georgia Douglas Johnson and Zora Neale Hurston as well as Wanuri Kahiu's negotiations of the agencies of dreams are discussed.